Contextual Teaching and Learning of Reading Skills in Indonesia: A Study of Higher Education English Lecturer’ Beliefs (International Journal of Education and Literature, 2025)
There is a mismatch between the policy of Contextual teaching and learning (CT&L) and learning in reading skills and the practice in the Indonesian higher education context. This is a case study that examines the beliefs of Indonesian higher education English lecturers about CT&L in English reading lessons. Context plays a pivotal role in English teaching, especially in reading, since it can connect teaching materials with students’ real-life context. The interviews revealed that teachers believe teaching English reading skills should be contextualized. However, these practices were not always easy because there were constraints in the form of decontextualized textbooks and uncontextualized teaching. The findings of this research would offer a recommendation for policy makers, English teachers in higher education context and future researchers interested in how to make English language learning in reading more contextual